DOMINANT FACTORS AFFECTING SHORT BIRTH INTERVAL BASED ON DATA OF IDHS 2017 - Nedra Wati Zaly; Mugia Bayu Raharja (Universitas Airlangga, 2022)
Short birth distances can be risky for the mother as well as for the baby. Mothers who experience pregnancy with too close a distance can be at risk of early rupture of amniotic fluid, bleeding, and anemia, while infants were at risk of low birth weight and death. To avoid such risks, couples of childbearing age should plan and determine the distance of pregnancy. The purpose of the study was to identify the most dominant factors that influence the incidence of short birth distances. Knowledge of birth distance is very beneficial for women's reproductive health. Furthermore, women are expected to delay pregnancy or provide birth distance after the previous birth. This study used secondary data from the Indonesian Health Demographics Survey (IDHS) 2017. The sample of this study is of women who gave birth to the last child born alive in the last five years when IDHS data were taken. The results of this study showed that the factor that most influences the occurrence of short birth distance is the survival status of the child after being controlled by other variables.